Outcomes and complications of intraoperative radiotherapy versus external beam radiotherapy for early breast cancer - Vahid Zangouri; Amirhossein Roshanshad; Aliyeh Ranjbar; Mahsa Izadi; Sara Rajaeifar; Ali Goodarzi; Hamid Nasrollahi (Cancer Reports, 2024)
Abstract Background Intraoperative radiotherapy (IORT) is an alternative for external beam radiotherapy (EBRT) for early stage breast cancer (BC). Herein, we compared outcomes, postoperative and post‐radiation complications of IORT and EBRT. Methods We conducted a cohort study to compare complications of IORT and EBRT in patients. A checklist of the complications of IORT and EBRT, was used to assess and post‐radiation complications and outcomes. Results Overall, 264 women (121 in IORT and 143 in EBRT group) with a mean (SD) age of 55 ± 8.6 years analyzed in this study. The IORT group (quadrantectomy + SLNB + IORT) had more severe post‐operative pain compared to the EBRT group (quadrantectomy + SLNB) (OR = 1.929, 95% CI: 1.116–3.332). Other postoperative complications, including edema, erythema, seroma, hematoma, and wound complications were not significantly different between the IORT and EBRT groups. EBRT was associated with higher rates post‐radiation complications, including erythema (95.8% vs. 21.5%), skin dryness (30.8% vs. 12.4%), pruritus (26.6% vs. 17.4%), hyperpigmentation (48.3% vs. 9.9%), and telangiectasia (1.4% vs. 0.8%). Multivariate analysis showed that erythema, skin dryness and pruritus, and hyperpigmentation were more severe in the EBRT group, while breast induration was higher in the IORT group (OR = 4.109, 95% CI: 2.242–7.531). Excellent, good, and fair cosmetic outcome was seen in 11.2%, 72%, and 16.8% of the patients in the EBRT group and 29.8%, 63.6%, and 6.6% in the IORT group, respectively, suggesting that the cosmetic outcome was significantly better in the IORT group (P < .001). There wasn't statistically significant difference in recurrence‐free survival and overall survival rates between two groups of patients who received either IORT or EBRT (P = .953, P = .56). Conclusion IORT is considered to have lower post‐radiation complications and better cosmetic outcomes in breast cancer patients. Therefore, IORT might be used as the treatment of choice in eligible patients.